Assessment of the technical condition of centrifugal pumping units by vibration parameters of bearing units - Sagatova, Laila; Bortebayev, Saiyn; Yelemessov, Kassym; Kolga, Anatoliy; Baskanbayeva, Dinara (International Journal of Innovative Research and Scientific Studies, 2025)
The aim of the study is to create a unified diagnostic criterion suitable for the effective assessment of the current condition of pumping equipment and for predicting the development of degradation processes. The article addresses issues related to vibration diagnostics and the evaluation of the technical condition of pump units. As part of the research, a sample of diagnostic data based on the vibration parameters of centrifugal pump units was used. The methodology for conducting vibration diagnostics on operating equipment using a vibration analyzer is described. To process the vibration signals, methods of direct spectrum analysis (autospectrum) and envelope spectrum analysis were applied, allowing for the determination of the signal's frequency components. The results of spectral analysis of the vibration signals from the bearing assemblies of the centrifugal pump unit are presented. The scientific novelty of the research lies in the development of a digital monitoring system for the operation of pump units, which represents an important step towards increasing the efficiency and reliability of pumping equipment. As a result of the study, fundamental diagnostic features for assessing the technical condition based on vibration parameters were developed, making it possible to create a unified diagnostic criterion for the assessment and prediction of the condition of centrifugal pump units.